2014
DOI: 10.1098/rsbl.2014.0538
|View full text |Cite
|
Sign up to set email alerts
|

Elevated carbon dioxide alters the plasma composition and behaviour of a shark

Abstract: Increased carbon emissions from fossil fuels are increasing the pCO 2 of the ocean surface waters in a process called ocean acidification. Elevated water pCO 2 can induce physiological and behavioural effects in teleost fishes, although there appear to be large differences in sensitivity between species. There is currently no information available on the possible responses to future ocean acidification in elasmobranch fishes. We exposed smallspotted catsharks (Scyliorhinus canicula) to either control condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 23 publications
5
75
0
Order By: Relevance
“…It is possible that L. erinacea from GB might be already 'pre-adapted' to acidification because of the elevated and frequent fluctuations in pH in their environment as a consequence of strong upwelling in the area (Pershing et al, 2001). Alternatively, it is possible that given that GoM skates have a reduced aerobic capacity, they might be more strongly affected by elevated plasma P CO2 and HCO 3 − (as seen in other elasmobranch species; Green and Jutfelt, 2014) as a consequence of increased acidification.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is possible that L. erinacea from GB might be already 'pre-adapted' to acidification because of the elevated and frequent fluctuations in pH in their environment as a consequence of strong upwelling in the area (Pershing et al, 2001). Alternatively, it is possible that given that GoM skates have a reduced aerobic capacity, they might be more strongly affected by elevated plasma P CO2 and HCO 3 − (as seen in other elasmobranch species; Green and Jutfelt, 2014) as a consequence of increased acidification.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in both localities, low pH increased the recovery time after exhaustive exercise. Possibly, acidification may have caused an elevation in P CO2 and HCO 3 − in the plasma (Green and Jutfelt, 2014), thereby increasing the costs associated with maintaining homeostasis. It is therefore possible that these additional costs might have significantly prolonged the time to recovery as young skates had to 'pay off' the oxygen debt after exhaustive anaerobic exercise (Svendsen et al, 2012;Webb, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P CO2 between 600 and 2000 µatm). The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%
“…The pattern that emerged was complete regulation of blood plasma pH and a 2-5 mmol l −1 increase in blood plasma [HCO 3 − ] Esbaugh et al, 2016Esbaugh et al, , 2012Green and Jutfelt, 2014;Heinrich et al, 2014;Heuer et al, 2016;Strobel et al, 2012) (Table 1). Only three studies measured blood plasma [Cl − ], but none of them found significant changes after exposure to OA-like conditions Green and Jutfelt, 2014;Heinrich et al, 2014). The lack of change in plasma [Cl − ] in marine fish could be due to the difficulty in accurately measuring small changes in [Cl − ] compared with 'background' control levels of 140-200 mmol l −1 (see Genz et al, 2008;Erlacher-Reid et al, 2011;Esbaugh et al, 2016;Lin et al, 2003;Toews et al, 1983;reviewed in Evans et al, 2005).…”
Section: Pharmacological Considerationsmentioning
confidence: 99%